ANALISIS FAKTOR PERUBAHAN DESAIN DALAM PROYEK PEMBANGUNAN JALAN LAYANG (FLYOVER) GANEFO (MRANGGEN) - Devita Gary Purnamasari; Indartono Rivai (FTSP Universitas Jayabaya, 2022)
Every project is rarely found that does not experience design changes. factors that affect a projectsuch as delays in project implementation due to design changes resulting in the project experiencing additional or reduced costs. The aims of the research are: (1) to analyze what factorsinfluence the delay in completing work, (2) to determine work items that experience changes inwork, (3) to calculate the costs due to changes in work items, (4) to research and identify to takesteps and determine appropriate actions to carry out project work when design changes occur.This study refers to the results of the questionnaire to determine the rankings of each factor andthe actions taken, BQ (Bill Of Quantity) and the price of the work unit. The calculation methoduses Haekal Hassan analysis, Jantje B. Mangare, Pingkan A.K.Pratasis descriptive statisticalmethod by determining the mean and calculating the Relative Importance Index (IKR) value. Theresults of the questionnaire obtained from 10 respondents showed that (1) the most influentialfactor was the poor coordination during the design process with a statistical value of 9.3. (2) Fromthe results of the calculation of the volume of work, there are 64 items that have changed. (3) theaddition of less costs and work results in no difference in costs after a change. (4) And the actionto carry out work that is very influential, namely the action of a request from the owner must havea clear order with a statistical result of 9.4.